THE EFFECT OF TIKTOK VIDEO IN LEARNING PRONUNCIATION SKILL - Dhea, Dhea Aprilia Nasution; , Nurlaili (Universitas Negeri Manado, 2023)
The purpose of this research was to found out the effect of Tiktok video in learning pronunciation skill at grade tenth of SMA Negeri 2 Lubuk Pakam. The sample of this research was 50 students took from the tenth grade of SMA Negeri 2 Lubuk Pakam, consisting of 25 students as an experimental class using Tiktok video as media and 25 students as a control class without Tiktok video. The method used in this research is quantitative method. In collecting data, researchers conducted pre-test and post-test by giving a test consisted of 20 vocabulary items for each test. The results of this research showed that there is a significant difference in students' pronunciation by using Tiktok videos. This is evidenced by the average score of the pre-test of the experimental class was 43.6 and the post-test was 67.68. While the mean score of the control class pre-test was 37.76 and the post-test was 48.68. In addition, the results of data calculations show that at a significance level of 0.05, t-observed of 4.80 with t-table of 1.677, or 4.80 > 1.677. Therefore, it can be concluded that learning pronunciation using Tiktok videos is effective.